Software testing : - Everett, Gerald D (Wiley-Interscience, 2007)
Software Testing presents one of the first comprehensive guides to testing activities, ranging from test planning through test completion for every phase of software under development, and software under revision. Real life case studies are provided to enhance understanding as well as a companion website with tools and examples